Glioblastoma‐educated mesenchymal stem‐like cells promote glioblastoma infiltration via extracellular matrix remodelling in the tumour microenvironment. Issue 8 (31st July 2022) - Kim, Seung‐Mo; Lim, Eun‐Jung; Yoo, Ki‐Chun; Zhao, Yi; Kang, Jae‐Hyeok; Lim, Eun‐Ji; Shin, Incheol; Kang, Seok‐Gu; Lim, Han Woong; Lee, Su‐Jae
Abstract: Background: The biological function of mesenchymal stem‐like cells (MSLCs), a type of stromal cells, in the regulation of the tumour microenvironment is unclear. Here, we investigated the molecular mechanisms underlying extracellular matrix (ECM) remodelling and crosstalk between MSLCs and glioblastomas (GBMs) in tumour progression. Methods: In vitro and in vivo co‐culture systems were used to analyze ECM remodelling and GBM infiltration. In addition, clinical databases, samples from patients with GBM and a xenografted mouse model of GBM were used. Results: Previous studies have shown that the survival of patients with GBM from whom MSLCs could be isolated is substantially shorter than that of patients from whom MSLCs could not be isolated. Therefore, we determined the correlation between changes in ECM‐related gene expression in MSLC‐isolatable patients with that in MSLC non‐isolatable patients using gene set enrichment analysis (GSEA). We found that lysyl oxidase (LOX) and COL1A1 expressions increased in MSLCs via GBM‐derived clusters of differentiation 40 ligand (CD40L). Mechanistically, MSLCs are reprogrammed by the CD40L/CD40/NFκB2 signalling axis to build a tumour infiltrative microenvironment involving collagen crosslinking. Importantly, blocking of CD40L by a neutralizing antibody‐suppressed LOX expression and ECM remodelling, decreasing GBM infiltration in mouse xenograft models. Clinically, high expression of CD40L, clusters of differentiation 40 (CD40) and LOX correlated with poor survival in patients with glioma. This indicated that GBM‐educated MSLCs promote GBM infiltration via ECM remodelling in the tumour microenvironment. Conclusion: Our findings provide mechanistic insights into the pro‐infiltrative tumour microenvironment produced by GBM‐educated MSLCs and highlight a potential therapeutic target that can be used for suppressing GBM infiltration. Abstract : In GBM patients, the survival rate of MSLC isolatable patients is lower than MSLC non‐isolatable patients, and ECM remodeling is more active. GBM‐secreted CD40L educates MSLCs, and educated‐MSLCs promote ECM remodeling for GBM infiltration via CD40/NFκB2/LOX signaling axis. When MSLCs are present in the GBM microenvironment, which could inhibition of GBM infiltration by treatment with CD40L blockade.